ENGLISH PHONOLOGICAL PROBLEMS ENCOUNTERED BY ALBANIAN LEARNERS - Zamira Metaj Alimemaj (European Scientific Journal, ESJ, 2014)
To acquire command of a foreign language, the learner should learn the basic skills of that language, i.e. listening, speaking, reading and writing. English can be difficult to learn because there are almost always exceptions to the "rules." For people of different cultures, some letters in English may be hard to pronounce as well. This can make the whole learning process more difficult. Correct pronunciation is a major key to language proficiency. Knowing the right vocabulary and when to use it simply is not enough. When you teach English as a second or foreign language, the primary goal is for students to communicate effectively. Pronunciation is basic to communication, and teachers should use the righ texercises to familiarize students with sounds and structure of English language. English pronunciation errors are sometimes specific to speakers of a certain language. However, many pronunciation errors are made by English language learners from different countries. Also, it is important to be aware that what may be considered a pronunciation error in an English-speaking country may not be so in another country where the main language is English. Even within different regions of a country, pronunciation of the same word in English may be very different. The aim of this paper is to present some of the difficulties the Albanian learners usually face in learning the English pronunciation.